Protein Adsorption to Surface Chemistry and Crystal Structure Modification of Titanium Surfaces - Ryo Jimbo; Mikael Ivarsson; Anita Koskela; Young-Taeg Sul; Carina B. Johansson (eJournal of Oral Maxillofacial Research)
Objectives: To observe the early adsorption of extracellular matrix and blood plasma proteins to magnesium-incorporated titanium oxide surfaces, which has shown superior bone response in animal models.Material and Methods: Commercially pure titanium discs were blasted with titanium dioxide (TiO2) particles (control), and for the test group, TiO2 blasted discs were further processed with a micro-arc oxidation method (test). Surface morphology was investigated by scanning electron microscopy, surface topography by optic interferometry, characterization by X-ray photoelectron spectroscopy (XPS), and by X-ray diffraction (XRD) analysis. The adsorption of 3 different proteins (fibronectin, albumin, and collagen type I) was investigated by an immunoblotting technique.Results: The test surface showed a porous structure, whereas the control surface showed a typical TiO2 blasted structure. XPS data revealed magnesium-incorporation to the anodic oxide film of the surface. There was no difference in surface roughness between the control and test surfaces. For the protein adsorption test, the amount of albumin was significantly higher on the control surface whereas the amount of fibronectin was significantly higher on the test surface. Although there was no significant difference, the test surface had a tendency to adsorb more collagen type I.Conclusions: The magnesium-incorporated anodized surface showed significantly higher fibronectin adsorption and lower albumin adsorption than the blasted surface. These results may be one of the reasons for the excellent bone response previously observed in animal studies.